2018
DOI: 10.1039/c8ra00158h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nitrogen doped carbon quantum dots/magnetite nanocomposites for efficient removal of methyl blue dye pollutant from contaminated water

Abstract: Herein, we report the green synthesis of magnetic, nitrogen doped carbon quantum dot/Fe3O4 NPs using aqueous lemon extract for the efficient removal of organic dye pollutants from contaminated water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Recently, a N-doped carbon quantum dot–magnetite nanocomposite was exploited for adsorption of methylene blue from waste water. 13 The N-doped carbon synthesized from ionic liquid@ZIF 8 was used for the removal of herbicides from water. 14 Perez-Aguilar et al reported the adsorption of Cd and Pb by N-doped multiwall carbon nanotubes prepared by the chemical vapor deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a N-doped carbon quantum dot–magnetite nanocomposite was exploited for adsorption of methylene blue from waste water. 13 The N-doped carbon synthesized from ionic liquid@ZIF 8 was used for the removal of herbicides from water. 14 Perez-Aguilar et al reported the adsorption of Cd and Pb by N-doped multiwall carbon nanotubes prepared by the chemical vapor deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the analytical performance, the influence of pH and response time on Cd 2+ adsorption using PVA-CDs film were evaluated. Figure 4a shows the % adsorption of Cd 2+ using PVA-CDs and uncoated CDs at different pH values (3)(4)(5)(6)(7)(8)(9)(10)(11). The adsorption efficiency of Cd 2+ for both PVA-CDs and uncoated CDs were found to rise in alkaline solutions, with a maximum % adsorption of 91 and 83, respectively.…”
Section: Effect Of Ph and Contact Time On CD 2+ Removalmentioning
confidence: 99%
“…Due to its toxic effects on human health, the separation and elimination of Cd 2+ from aquatic media is still a hot research topic. Among the solutions, zeolites [5], polymeric compounds [6] and carbon-based materials [7,8] are the most widely used sorbents for the removal of chemical pollutants, due to their large surface area and tunable pore size.…”
Section: Introductionmentioning
confidence: 99%
“…Such structure successfully removed methylene blue from aqueous solution. Tadesse et al [7] developed a magnetic nanocomposite adsorbent by combining nitrogen-doped lemon juice-derived carbon quantum dot and Fe 3 O 4 (Fe 3 O 4 @NCQDs NCS), which was used to remove methylene blue pollutants from aqueous solution and the system exhibited a good adsorption performance. In the attempt to remove Cu(II) and Pb(II) from aqueous solution, Yao et al [8] synthesized an adsorbent by grafting dialdehyde cellulose (DAC) on the GO template using triethylenetetramine as the crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%
“…Such structure successfully removed methylene blue from aqueous solution. Tadesse et al . developed a magnetic nanocomposite adsorbent by combining nitrogen‐doped lemon juice‐derived carbon quantum dot and Fe 3 O 4 (Fe 3 O 4 @NCQDs NCS), which was used to remove methylene blue pollutants from aqueous solution and the system exhibited a good adsorption performance.…”
Section: Introductionmentioning
confidence: 99%